Citrus transcription factor CsERF1 is involved in the response to citrus tristeza disease - Chen, Qi; Yan, Fulin; Liu, Jing; Xie, Zhipeng; Jiang, Junyao; Liang, Jiamei; Chen, Jing; Wang, Huanhuan; Liu, Jinxiang (Frontiers in Plant Science, 2025)
IntroductionCitrus tristeza virus (CTV) is a threat to the citrus production and causes severe economic losses to the citrus industry. Ethylene response factors (ERFs) play important roles in plant growth and stress responses. Although ERF genes have been widely studied in model plants, little is known about their role in biological stress responses in fruit trees, such as citrus. CsERF1 belongs to the citrus AP2/ERF transcription factor family.MethodsTo determine the role of CsERF1 on CTV resistance in citrus and the effects of the exongenous hormone application on CsERF1 in citrus, the expression of related genes was quantitatively analyzed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) in this study.ResultsThe expression profile showed that the expression level of CsERF1 in roots was significantly lower under CTV infection than in healthy plants, while the expression level in stems was significantly increased. CsERF1 responded to exogenous salicylic acid (SA) and methyl jasmonate (MeJA) treatments. The CTV titer in RNAi-CsERF1 transgenic sweet orange plants significantly increased. Furthermore, CsERF1-overexpressing and RNAi-CsERF1 transgenic sweet orange plants exhibited differential expression of genes involved in jasmonic acid (JA) and SA signaling.DiscussionThese results suggest that CsERF1 mediates CTV resistance by regulating the JA and SA signaling pathways. The results of this study provide new clues as to the citrus defence response against CTV. It is of great significance to create citrus germplasm resources resistant to recession disease.